Novel TBX3 mutation in a family of Cypriot ancestry with ulnar-mammary syndrome. Issue 2 (April 2017) - Tanteles, George A.; Nicolaou, Nayia; Syrimis, Andreas; Metaxa, Rafaella; Nicolaou, Michael; Christophidou-Anastasiadou, Violetta; Skordis, Nicos
Abstract : Ulnar-mammary syndrome (UMS) is an autosomal dominant disorder resulting from TBX3 haploinsufficiency. It typically affects limb, apocrine gland, hair, tooth and genital development and shows marked intrafamilial and interfamilial variability in phenotypic expression. We report a family (twin brothers and their father) affected with UMS because of a novel TBX3 mutation. The twin brothers showed classical features of UMS, whereas their father was mildly affected. The c.1423C>T (p.Q475*) nonsense mutation in exon 6 of the TBX3 gene identified in the patients by targeted Sanger sequencing is predicted to lead to premature termination of translation. This is the first report of a Cypriot family with UMS resulting from a novel TBX3 mutation. This report provides additional evidence in support of the rich variability in phenotypic expression, the mutational heterogeneity and ethnic diversity associated with this rare condition.